A Combined Pulse Driving Waveform With Rising Gradient for Improving the Aperture Ratio of Electrowetting Displays - Tian, Lixia; Bai, Pengfei (Frontiers in Physics, 2021)
As a reflective display technology, electrowetting displays (EWDs) have the advantages of paper-like display, low power consumption, fast response and full color, but the aperture ratio of EWDs is seriously affected by oil dispersion and charge trapping. In order to improve the aperture ratio and optimize the display performance of EWDs, a combined pulse driving waveform with rising gradient design was proposed. Firstly, an initial driving voltage was established by the threshold voltage of oil film rupture (Vth). And then, a rising gradient was designed to prevent oil from dispersing. At last, the oil splitting and movement were controlled to achieve the target aperture combined with the pulse waveform. Experimental results showed that the oil dispersion of EWDs can be effectively improved by using the proposed driving waveform, the aperture ratio of EWDs was increased by 3.16%, and the stability was increased by 71.43%.